Exploring the Tourism Potential and Challengeso Integrating Local Wisdom in Sabang, Indonesia - Tumangger, Hasrioni Dosma Arih; Eddyono, Fauziah (Ilomata International Journal of Social Science, 2025)
Sabang, located at the westernmost tip of Indonesia, is a tourism destination that illustrates the complex interaction between local Islamic governance and global travel behavior. The implementation of Qanun, or regional Islamic bylaws, poses distinct challenges for tourism development, particularly in accommodating visitors unfamiliar with these regulations. This study analyzes how Qanun, destination branding, and tourist attitudes influence travel decisions related to Sabang. Using a quantitative descriptive design, data were collected from 100 potential travelers in Jakarta. The results show that tourist attitudes significantly affect travel decisions, whereas Qanun and destination branding do not have direct effects. The findings underscore the importance of adaptive governance and culturally responsive communication in promoting inclusive tourism. By aligning religious regulations with global market expectations, this study contributes to the development of sustainable and culturally sensitive tourism policies that harmonize local wisdom, visitor experience, and destination competitiveness.